(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Skull-base tumors (SBTs) of the middle and anterior fossae cause compressive optic neuropathy which is accompanied by decreased visual acuity, bitemporal visual field defects and development of primary descending optic atrophy (OA). Optical coherence tomography (OCT) is an up-to-date non-invasive imaging modality that allows objective assessment of stereometric parameters of the optic nerve. Reduced peripapillary retinal nerve fiber layer thickness, reduced neuroretinal rim area, and reduced macular ganglion cell complex (GCC) thickness are characteristic changes in retinal morphology in compressive optic neuropathy. Purpose: To analyze the changes in OCT-measured morphological and structural parameters of the retinal GCC in patients with primary optic atrophy due to compression by SBTs. Material and Methods: This study included 57 patients (114 eyes) who received treatment for SBT and loss of visual acuity and/or visual fields at the Romodanov Neurosurgery Institute during 2017 through 2019. Patients underwent clinical and neurological, eye, otoneurological, neiroimaging and laboratory examination. Results: There was a significant difference in average GCC thickness among any subgroup (Subgroup 1, 101.69 ± 4.01 nm; Subgroup 2, 98.6 ± 2.28 nm; Subgroup 3, 90.4 ± 3.92 nm; Subgroup 4, 80.8 ± 3.72 nm; Subgroup 5, 71.86 ± 5.31 nm) and controls (113.01±3.86 nm) (p < 0.05). Although no abnormalities in visual function were found in eyes of Subgroup 1 (no chiasmal syndrome before and after treatment), these eyes exhibited GCC thinning in superior nasal and inferior nasal segments (99.24±3.21 nm and 96.21±3.18 nm, respectively), which is an early sign of compressive optic neuropathy. Conclusion: Binasal thinning of the GCC (a subclinical sign of chiasmal compression) reflects early mild damage to axons, precedes visual field defects and optic atrophy, and is an early indication for SBT removal.